The Effectiveness of Online Learning in the Subject of Fiqh on the Learning Outcomes of Students at Madrasah Aliyah Madani Alauddin - Fitriani, Ika; Arsyad, Azhar; Marjuni, Marjuni (Jurnal Mercusuar, 2021)
The aim of this study is to determine whether online learning in the subject of Fiqh is effective towards the learning outcomes of students at MA Madani Alauddin. This type of research is an ex post facto study using a quantitative methodology approach. The respondents in this study were 98 individuals obtained using a saturated sample, meaning that all individuals in the population were used as samples. The data was collected using questionnaires and documentation formats, which were analyzed using descriptive and inferential statistics by conducting T-tests. Based on the results of inferential statistics hypothesis testing, the effectiveness of online learning on student learning outcomes was found to be 31%, which falls under the weak correlation category, while the remaining 69% was influenced by other variables. Efforts made by Fiqh teachers to improve student learning outcomes, which were also supported by data obtained from the learning outcomes, indicate that online learning falls under the low category. Meanwhile, the effectiveness of online learning at MA Madani Alauddin, which was obtained from the questionnaire data, falls under the moderate category. For Fiqh teachers, educators should participate more in training forums on various creations and innovations to create various online learning media that make students even more interested in learning online. Additionally, educators should actively monitor students and provide education to parents related to this online learning. For parents and students, in conducting online learning, the role of parents is essential, both in providing learning facilities and accompanying their children in the use of gadgets, so that gadgets are only used for the purposes of online learning.